(untitled) (Research, Society and Development, 2020)
A differential factor in cattle production is the understanding of the individual contribution of fatty acids and the role of lipids in ruminants, both in the form of analysis (fatty acid or ether extract), concepts related to the characteristics of omega 3, omega 6 and linoleic acid conjugated in bio-hydrogenation, post-absorption metabolism, as well as in the content and composition of fatty acids in relation to the dry matter of foods. It is known that several factors can affect the content, digestibility and degradability of the fibers present in the forage, and the same occurs with lipids. The differences between the values of the compounds present in the lipids can occur depending on the environment, region of the country or harvest stage and for this reason, it is important to obtain an analysis of the composition of fatty acids in lipidic foods, so that in this way it is possible to optimize the use of this nutrient in the diet of ruminant animals. Therefore, the purpose of this review will be to bring up the discussion on the topic and address an understanding of the content and composition of fatty acids in the ingredients that make up the diet of ruminant animals, with emphasis on the influence on productive performance, immunonutrition, and on the product final (meat or milk).